Financial Management of the Regional Public Service Agency at Dr. Sam Ratulangi Tondano Regional General Hospital - Mandagi, Kelly D. H.; Bogar, Wilson; Mokat, Jetty E. H. (Technium Social Sciences Journal, 2025)
This study aims to analyze the financial management of the Regional Public Service Agency (BLUD) at the Dr. Sam Ratulangi Tondano Regional General Hospital (RSUD), focusing on financial information systems and compliance with accounting standards as well as audit and supervision mechanisms. The background of this study is based on the importance of the flexibility of BLUD budget management to remain accountable and transparent in accordance with the Regulation of the Minister of Home Affairs No. 79 of 2018, as well as the real challenges faced by the RSUD in terms of financial systems that have not been integrated and the lack of technological capacity and supporting Human Resources. This research uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation studies. Research informants consisted of leaders, financial staff, and hospital internal auditors. The data were analyzed using data reduction techniques, data presentation, and conclusion drawing of the Miles and Huberman model, and tested for validity through triangulation of sources and methods. The results showed that financial management at RSUD Tondano is still done manually without the support of an integrated financial information system. This results in recording delays, data inaccuracies, and limited transparency in financial reporting. In addition, financial reports are not yet accessible to all relevant units and are only available to leaders and auditors. Although reports have been prepared based on the Government Accounting Standards (SAP) format, limited human resources and infrastructure have led to suboptimal financial accountability. Internal audits are conducted irregularly and external audit recommendations have not been followed up optimally due to budget constraints. This study recommends the implementation of a digital-based integrated financial information system and increasing the capacity of Human Resources so that financial management at RSUD Tondano becomes more efficient, transparent, and accountable for improving the quality of health services to the community.